A relação entre o comportamento verbal e o não verbal de crianças na escolha do lanche - Melo, Maria Elisa Midlej Pereira de (2007)
Many studies have been analyzing treatments that intervene with the occurrence of correspondence between verbal and non verbal behavior. Nevertheless, the role of verbalization for the emission of the correspondent non verbal behavior, in the studies about correspondence between saying and doing, is not clear yet. The present work had the purpose to combine some treatments already used by some of the studies, with the intention to verify which would be the role of verbalization in the control of non verbal behavior, using a different target behavior than those that have been used in the most part of the studies, and introducing some modifications in the procedure and in the experimental design. The target behavior was the choice of food, considered healthful for the snack. 23 children between 5 and 6 years, with normal development, that studied in the same classroom of a Council School for children, participated of the study. The experimental conditions were: baseline, reinforcement of verbalization, reinforcement of compliance (experimenter s verbalization), reinforcement of correspondence, reinforcement of doing and reinforcement of verbalization 2. The children were divided in 3 groups, with 8, 5 and 7 participants. The sequence of presentation of the treatments varied between the groups. A of multiple baseline design between participants of the same group was used. The results pointed that during of baseline the frequency of choice of more healthful snacks is low, but the frequency of correspondence between verbal and non verbal behavior is high. During the phase of reinforcement of verbalization, the frequency of choice of more healthful snacks is low, and so is the frequency of correspondence between verbal and non verbal behavior. In the phase of reinforcement of doing, the frequency of choice of more healthful snacks is low only when this phase precedes the reinforcement of correspondence and the reinforcement of compliance. In the phases of reinforcement of compliance and reinforcement of correspondence, the frequency of choice of more healthful food increases for the three groups. In the phase of reinforcement of verbalization 2, the frequency of choice of more healthful food was higher than in the phase of reinforcement of verbalization, being, therefore, higher the correspondence frequency. The present study suggests that verbalization has an important role to provide the target response; however it can proceed from the participant as well from the experimenter